The Future of Food Tourism Foodies, Experiences, Exclusivity, Visions and Political Capital - Albrecht, Julia N.; Fields, Kevin; McMahon-Beattie, Una; Meethan, Kevin; Yeoman, Ian (Aspects of Tourism, 2015)
This book presents a systematic and pattern-based explanation of food tourism, focusing on how and why change could occur and what the implications could be. In the future will food tourism involve food grown in the laboratory or a more authentic experience associated with place and history? The book’s approach to the future has focused on explanation; the contributors look for the causes, trends and theoretical concepts that explain change, thus attempting to justify and explore the future. Scenarios are used to explore alternative futures and the book examines the implications for the future of food tourism and highlights future research avenues. This book is primarily aimed at postgraduate students and researchers in the field of tourism studies